Conjunctival impression cytology in dogs - Bolzan, A. A.; Brunelli, ATJ; Castro, M. B.; Souza, M. A.; Souza, J. L.; Laus, J. L. (Blackwell Publishing, 2005)
Objective Ocular conjunctivas of healthy dogs were studied by conjunctival impression cytology for evaluation of feasibility, protocol standardization, and normal cytologic pattern recognition of this technique.Animals studied Twenty healthy, adult, cross-breed dogs.Procedures Samples of the bulbar conjunctiva were collected after instillation of topical anesthetic drops at the ocular surface. Impression cytology was performed by applying asymmetric strips of Millipore filter on the superior temporal bulbar conjunctiva near the limbus. The filter strip was gently pressed against the conjunctiva for 5 s and removed with a peeling motion. Samples were immediately fixed in 95% ethyl alcohol, stained with periodic acid-Schiff and hematoxylin, and mounted on slides cover-slipped using synthetic resin. The slides were examined by light microscopy.Results Microscopic examination of the impressions revealed superficial, intermediate and basal epithelial cells arranged in sheets. Keratinized epithelial cells, goblet cells and leukocytes, as well as cellular debris and mucus were observed.Conclusions Feasibility of impression cytology for sampling the bulbar conjunctiva of the dog and the standardization the the proposed protocol was shown. The results allowed the recognition the the normal cytologic pattern of healthy conjunctivas in dogs.
Keywords: Conjuntiva; dog; impression cytology